Simulasi Tegangan dan Perubahan Bentuk Pada Rangka Sepeda Air Hamors Menggunakan Software Solidwork 2013 - Hendra Saputra; Riza Ahmad Zulkarnain (Politeknik Negeri Batam, 2015)
Frame is the most important part of the bike, the ergonomics of bike is very determined of designing the shape and dimensions of the frame. Frame shape are required to fullfill the comfort aspect without ignore the factor of the power of the bike frame itself. The strength of the frame is a something that should be a primary concern , because the strength of frame extremely affect the rider safety. Hamors water bike frame is designed by changing shape of a frame mountain bike (MTB). The changes are intended to make bicycle frame can be combined with a float . To find out the safety and strength of a frame do the simulation process , by providing load variation in order to use the material Black Steel Pipe (AISI 1080), Steel Alloys and ST 37 Pipe (DIN 1.0037). Simulation process is done by using the software SolidWorks 2013. The highest maximum stress occurs in the frame of a water bike hamors with material AISI 1080 with a maximum stress is (60kg = 52,19 N/mm2 (Mpa), maximum displacement 1,14 mm and 70kg = 60,61 N/mm2 ( MPa ), maximum displacement 1,32 mm) and still be able to support the weight of (safe). The simulation results showed that the water bike frame with three types of materials are able to withstand the load (safe). There is a change in the form of order due to variations in load and material to the stress distribution and deformation frame simulated.